Method and apparatus for nonlinear compensation in an active noise control system - Raja Ahmad, Raja Mohd Kamil; Sahib, Mouayad Abdulredha; Dehkordi, Sepehr Ghasemi (2013)
A self tuned apparatus (100) for active noise control includes a first transducer (105) and a second transducer (110), a noise controlling module (115), a power amplifier (120) and a first loudspeaker (125) and a second loudspeaker (130) coupled to the power amplifier (120). The noise controlling module (115) is coupled to the first transducer (105) and the second transducer (110). The power amplifier (120) is coupled to the noise controlling module (115). Particularly, the noise controlling module (115) employs at least one control algorithm.